Sistem Pengelolaan Sarpras Berbasis RFID di SMK Widya Praja Ungaran - B. Suhartono; Yunus Ridwan (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
In the current era of globalization and technology, computers, RFID are examples of information technology tools that are indispensable for meeting human needs in almost every aspect of life, including the management of infrastructure and equipment lending.According to direct research at Widya Praja Ungaran Vocational School, there are only two workers who handle facilities and infrastructure. In carrying out their work assignments, they still experience difficulties. Excess workload and the process of borrowing tools that still lacks a sense of responsibility, so that the results of the work are not maximized.The existence of increasingly sophisticated technology, the management of infrastructure and equipment lending can be done with the help of technological tools that will be implemented in this school. This research aims to make it easier to administer, because this school has not yet added a new workforce.This research can be designed with the help of software (Bootstrap, MySql), programming (PHP, Arduino IDE) and equipment (NodeMCU ESP8266, RFID, LCD, I2C, buzzer, power supply, breadboard, jumper cables, resistors, LEDs) to provide data information. more accurate, effective, efficient and provide a good working atmosphere in this school. It is hoped that this research can reduce work overload and create a sense of responsibility in borrowing equipment, using local networks (wifi / handphone) and computers or laptops, with the research method used is research and development (R&D).